Resting energy expenditure in patients with COPD: Agreement between predicted equations and indirect calorimetry - Santi Silairatana; Sirakarn Tejavanija (Clinical Nutrition Open Science)
Background: Accurate, individualized energy and protein, as well as other nutrient components, are highly important to improve the nutritional status and increase muscle mass in COPD patients, particularly those having nutritional depletion and experiencing a loss of lean body mass. Despite having a high degree of accuracy, the determination of energy requirement using indirect calorimetry (IC) is often limited by its availability and therefore predictive equations are used as alternatives. This study aims to determine agreements between measured REE using IC and estimated REE obtained from predictive equations that are commonly used in clinical practice among COPD patients, both with and without malnutrition or sarcopenia. Methods: A cross-sectional study was conducted among clinically- and spirometry-confirmed COPD patients from August 2022 to January 2023. IC, bioelectrical impedance analysis, anthropometry, handgrip strength measurement as well as biochemical tests (serum albumin, ESR and CRP) were performed in all participants to collect data for analysis of correlation and agreement between two methods. The predictive equations tested included the Harris-Benedict, Schofield, Institute of Medicine, Mifflin St Jeor, Westerterp, Morikawa, and Moore & Angelilo equations. The differences of energy expenditure between groups with and without malnutrition or sarcopenia were tested statistically using an independent-sample t-test and Mann-Whitney U test, while correlations, as well as degree of agreement between methods were analyzed and reported using Bland-Altman plots. The significant two-tailed P value was set at <0.05. Results: A total of 84 patients with COPD (25% women) were included in the study. the average age was 71±14 years. The average spirometric values were as follows: FEV1/FVC 61.5±9%, FEV1 64±15% of predicted, and FVC 85.52±13.9% of predicted. Among the COPD patients with sarcopenia, the average REE was significantly lower than patients without sarcopenia (1154±238 kcal/day vs 1230±234 kcal/day, P=0.01). No statistically significant differences of the average measured REE between COPD patients with and without malnutrition or high inflammatory markers was observed. Bland-Altman plots demonstrated that, among the equations tested, estimated REE using Westerterp equation provided the highest accuracy rate (58.3%) followed by the Scofield equation (57.1%) with the bias and limit of agreement of 26 kcal/day and -288 to +340 kcal/day for Westerterp and +32 kcal/day and -353 to +289 kcal/day for Schofield equation, respectively. Conclusion: Estimation of REE using Schofield and Westerterp equation provides better accuracy rate and lower level of bias in COPD patients across various clinical conditions and may be used for estimation when IC is not available. When FFM measurement is available, Nordenson equation provide the highest accuracy of estimates.